Al-Wujūhu Al-Ḍoifaħ ‘Indal Imām Ibn Juzay Fī Tafsīr Min Sūraħ An-Nazi`at Ila Sūraħ At-Ṭariq: الوجوه الضعيفة عند ابن جزي الكلبي في تفسيره التسهيل لعلوم التنزيل من سورة النازعات إلى سورة الطارق - Ikhsan, Ahmad Nur; Al-Maswari, Abdulkhaleq Obad Mohammed; Mubarok, Wildan Fata (Civilization Research: Journal of Islamic Studies, 2023)
This study aims to determine the weak arguments according to Imam Ibn Juzay in his interpretation. This study follows an analytical descriptive approach, by following the arguments weakened by Imam Ibn Juzay in his interpretation of the facilitation of the sciences of revelation, then collecting, classifying, presenting, and analyzing them, in accordance with their origins and rules of interpretation. This study proves that the arguments weakened by Imam Ibn Juzay in his tafsir from Sūraħ Al-An-Nazi'at to Sūraħ At-Tariq number eleven places. This study reveals that the arguments weakened by Imam Ibn Juzay are not all correct, and the knowledge of the arguments weakened by Imam Ibn Juzay in his tafsir is something that should be considered and explored by tafsir teachers.